2021
DOI: 10.1016/j.dscb.2021.100021
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1-Nrf2 axis is activated upon murine β-coronavirus infection in the CNS

Abstract: Coronaviruses have emerged as alarming pathogens owing to their inherent ability of genetic variation and cross-species transmission. Coronavirus infection burdens the endoplasmic reticulum (ER.), causes reactive oxygen species production and induces host stress responses, including unfolded protein response (UPR) and antioxidant system. In this study, we have employed a neurotropic murine β-coronavirus (M-CoV) infection in the Central Nervous System (CNS) of experimental mice model to study the role of host s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Studies have reported that DJ‐1 can mediate cell survival by activating the extracellular signal‐regulated kinase (Erk) pathway and the downstream nuclear factor erythroid 2‐related factor 2 (Nrf2) pathway. 30 , 31 Our western blotting results also showed that the phosphorylation of Erk1/2 and its downstream transcription factor Elk‐1 was upregulated by 250 nM tFNAs‐DJ‐1‐saRNA in H 2 O 2 ‐treated HUVECs (Figure 5D ). On the other hand, 125 nM tFNAs‐DJ‐1‐saRNA could also efficiently promote the expression of the phosphorylation of Akt, Nrf2, and heme oxygenase‐1 (HO‐1) in ARPE‐19 cells (Figure 5E ).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Studies have reported that DJ‐1 can mediate cell survival by activating the extracellular signal‐regulated kinase (Erk) pathway and the downstream nuclear factor erythroid 2‐related factor 2 (Nrf2) pathway. 30 , 31 Our western blotting results also showed that the phosphorylation of Erk1/2 and its downstream transcription factor Elk‐1 was upregulated by 250 nM tFNAs‐DJ‐1‐saRNA in H 2 O 2 ‐treated HUVECs (Figure 5D ). On the other hand, 125 nM tFNAs‐DJ‐1‐saRNA could also efficiently promote the expression of the phosphorylation of Akt, Nrf2, and heme oxygenase‐1 (HO‐1) in ARPE‐19 cells (Figure 5E ).…”
Section: Resultsmentioning
confidence: 64%
“…Studies have reported that DJ-1 can mediate cell survival by activating the extracellular signal-regulated kinase (Erk) pathway and the downstream nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. 30,31 Our western blotting results also showed that the phosphorylation of Erk1/2 and its downstream transcription factor Elk-1 was upregulated by 250 nM tFNAs-DJ-1-saRNA in H 2 O 2 -treated HUVECs (Figure 5D).…”
Section: Tfnas-dj-1-sarna Protect Against Oxidative Injurymentioning
confidence: 60%
“…They also demonstrated that the alteration of DJ-1, an oxidant-sensing molecule, was the first instance in M-CoV. 94 Therefore, Enrichr results of the GDS1028 dataset showed higher expression levels of SNCA and PARK7 in the PBMCs of patients with SARS (COVID-19) compared to healthy individuals. It could be argued that the parallel expression of these genes in PD and COVID-19 would probably lead to an increase in PD symptoms due to infection with COVID-19.…”
Section: Discussionmentioning
confidence: 97%